2016
DOI: 10.18632/oncotarget.14056
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of resveratrol against mancozeb induced apoptosis damage in mouse oocytes

Abstract: Mancozeb, a mixture of ethylene-bis-dithiocarbamate manganese and zinc salts, is one of the most widely used fungicides in agriculture. Mancozeb could lead to mitochondria dysfunction, cellular anti-oxidation enzymes depletion and apoptotic pathways activation. Previous studies indicated the exposure of mancozeb through mother would lead to irregular estrous cycles, decreased progesterone levels, reduced litter sizes, and more frequent delivery of dead fetuses. In this study, we investigated mancozeb inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 50 publications
4
37
0
Order By: Relevance
“…Oral mancozeb exposure (800 mg/kg/day) also reduces litter size and weight with a relevant decrease in ovary weight [45]. In this context, there was also an increase in atretic follicles and a reduction in healthy oocytes.…”
Section: In Vivo Experimental Studiesmentioning
confidence: 93%
See 3 more Smart Citations
“…Oral mancozeb exposure (800 mg/kg/day) also reduces litter size and weight with a relevant decrease in ovary weight [45]. In this context, there was also an increase in atretic follicles and a reduction in healthy oocytes.…”
Section: In Vivo Experimental Studiesmentioning
confidence: 93%
“…In this context, there was also an increase in atretic follicles and a reduction in healthy oocytes. Liu et al also reported ultrastructural changes in Germinal Vesicle (GV) oocytes due to mancozeb administration [45]. Noteworthy, is the decrease in the number of pronuclei and two-cells of parthenogenetic activated oocytes and the alteration in actin expression levels [45].…”
Section: In Vivo Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting symptoms are convulsions, slurred speech, confusion, slowed heartbeat etc. Mancozeb is reported to be an established carcinogen (FAO/WHO 1993, Vettorazzi et al 1995, Liu et al 2016. Mancozeb is reported to cause teratogenic, carcinogenic and goitrogenic effects on mammals.…”
Section: Introductionmentioning
confidence: 99%